Reported reasons for breakdown of marriage and cohabitation in Britain: Findings from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3) - Gravningen, Kirsten; Mitchell, Kirstin R.; Wellings, Kaye; Johnson, Anne M.; Geary, Rebecca; Jones, Kyle G.; Clifton, Soazig; Erens, Bob; Lu, Michelle; Chayachinda, Chenchit; Field, Nigel; Sonnenberg, Pam; et al. (PLOS ONE, 2017)
Objectives Breakdown of marriage and cohabitation is common in Western countries and is costly for individuals and society. Most research on reasons for breakdown has focused on marriages ending in divorce and/or have used data unrepresentative of the population. We present prevalence estimates of, and differences in, reported reasons for recent breakdown of marriages and cohabitations in Britain. Methods Descriptive analyses of data from Britain’s third National Survey of Sexual Attitudes and Lifestyles (Natsal-3), a probability sample survey (15,162 people aged 16–74 years) undertaken 2010–2012, using computer-assisted personal interviewing. We examined participants’ reported reasons for live-in partnership breakdown in the past 5 years and how these varied by gender and partnership type (married vs. cohabitation). Results Overall, 10.9% (95% CI: 9.9–11.9%) of men and 14.1% (13.2–15.0%) of women reported live-in partnership breakdown in the past 5 years. Mean duration of men’s marriages was 14.2 years (95% CI: 12.8–15.7) vs. cohabitations; 3.5 years (3.0–4.0), and for women: 14.6 years (13.5–15.8) vs. 4.2 years (3.7–4.8). Among 706 men and 1254 women reporting experience of recent breakdown, the reasons ‘grew apart’ (men 39%, women 36%), ‘arguments’ (27%, 30%), ‘unfaithfulness/adultery’ (18%, 24%, p<0.05), and ‘lack of respect/appreciation’ (17%, 25%, p<0.05) were the most common, irrespective of partnership type. A total of 16% of women vs. 4% of men cited domestic violence. After adjusting for age at interview and duration of partnership, there were no significant differences in reasons given for breakup by partnership type, except that men more commonly cited ‘moving due to changing circumstances’ as a reason for a cohabitation ending than for a marriage (AOR = 3.78, 95% CI: 1.08–13.21); and among women, ‘not sharing housework’ (0.54, 0.35–0.83) and ‘sexual difficulties’ (0.45, 0.25–0.84) were less commonly cited as reasons for cohabitation ending than marriage. Conclusion These representative data on recently ended marriages and cohabitations among men and women in Britain show that there were more similarities than differences in the reasons reported for breakdown across partnership type. For both marriages and cohabitations, cited reasons relating to communication and relationship quality issues were most common, followed by unfaithfulness/adultery. Our findings support a focus on relationship quality, including communication and conflict resolution, in preventive and therapeutic interventions addressing breakdown of live-in partnerships.